Financial institutions performance evaluation in a unique developing market using TOPSIS approach - Sami Al Kharusi; Eşref Savaş Başci (Banks and Bank Systems, 2017)
Using Technique for Order Performance by Similarity to Ideal Solutions (TOPSIS) approach for the data from 2011 to 2015, the authors investigate the financial performance of 16 different financial institutions in Oman that include nine commercial banks, three specialized banks, two investment companies, and two finance companies. They find that the one investment company, Dhofar International Development and Investment Holding Co., was more efficient in 2015 and 2011. Moreover, Oman Housing Bank was more efficient in 2013 and 2014, while Ahli Bank was more efficient in the year 2012. In contrast, Bank Muscat that has the largest total assets was ranked number 16 for the years 2013, 2014 and 2015. As a result of Spearman’s Rho (Rank-Order) Correlation, all ranked results are related to other years. If a bank is at placement in level, it can be affected by year before or year after. But Oman banks’ correlations shows that there are 2 different periods as effecting one year to the other. Keywords: financial institutions performance, TOPSIS, emerging markets, efficiency, decision making criteria. JEL Classification: G21, G23, L25